2003
DOI: 10.1046/j.1440-1754.2003.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal perforation in preterm neonates: Not an innocent bystander

Abstract: Oesophageal perforation is a rare but important complication of modern neonatal intensive care setting. The diagnosis of OP should be considered in infants who present with sudden/acute deterioration in their respiratory status following procedures involving pharyngeal region. Conservative management in an otherwise uncomplicated case leads to complete recovery in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 11 publications
(32 reference statements)
3
34
0
Order By: Relevance
“…This dual‐centre cohort study reinforces the appropriateness of a conservative approach to management for most neonates with isolated oesophageal perforation. There has been a recent trend towards this non‐operative management, with successful outcomes . Our patient cohort was predominantly managed conservatively, with only two neonates requiring thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dual‐centre cohort study reinforces the appropriateness of a conservative approach to management for most neonates with isolated oesophageal perforation. There has been a recent trend towards this non‐operative management, with successful outcomes . Our patient cohort was predominantly managed conservatively, with only two neonates requiring thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported variable clinical presentations of oesophageal perforation . Shah et al . described symptomatic presentations in all neonates with oesophageal perforation.…”
Section: Discussionmentioning
confidence: 99%
“…No definitive site of perforation was visualized. et al previously reported a statistically significant increased duration to full oral feeding for ten preterm infants with esophageal perforation [12].…”
Section: Discussionmentioning
confidence: 91%
“…Subsequently, numerous case series have documented additional patients with upper aerodigestive injury following perinatal airway instrumentation; although reported in both term and preterm infants, an overall predilection for premature neonates is evident in the literature [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Reflexive cricopharyngeal muscular constriction and esophageal narrowing and compression against cervical vertebrae with extension of the infant head have been hypothesized to make the posterior hypopharynx and esophageal introitus the site of the vast majority of these injuries [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…A lateral view taken at the same time is also helpful for the diagnosis 16) . The need for contrast radio graphy for a diagnosis has been questioned by several authors 3) . In our case, a Gastrograffin contrast radiogram confirmed the diagnosis, but this may have been a causative factor for the hydrothorax that developed thereafter.…”
Section: Discussionmentioning
confidence: 99%